Microvascular pathology of Friedreich cardiomyopathy. (September 2019) - Koeppen, A; Sossei, A; Travis, A; Kleinhenz, E; Mazurkiewicz, J; Feustel, P; Qian, J
Abstract : Nikolaus Friedreich (1877) was aware of heart disease in his patients but thought it was unrelated to the neurological disorder. In 1946, Dorothy Russell considered cardiomyopathy an integral part of Friedreich ataxia (FA). In addition to sparse inflammatory infiltration, sections show fibrosis and capillary hyperplasia. We examined the left ventricular walls of 41 homozygous FA patients aged 10–87 and 21 controls aged 2–69. An antibody to CD34 enabled quantitative capillary profile counts for a comparison with cardiomyocyte counts in the same field. Mean capillary counts in normals were 1926±341/mm 2, and the median ratio of capillaries to cardiomyocytes was 1.0 (interquartile range [IQR]: 0.9-1.2). In FA, however, the number of cardiomyocytes/mm 2 was less, and the median ratio of capillaries to heart fibers was 2.0 (IQR 1.4-2.4). There was a significant correlation of the higher guanine-adenine-adenine trinucleotide length (shorter allele, GAA1) with the younger age of onset, shorter disease duration, and lower cardiomyocyte counts. The ratio of capillaries to heart fibers was higher in patients with long GAA1 repeat expansions (e.g., 3.31 in GAA1 of 1200). Double-label immunofluorescence for CD34 and S100A4 revealed co-expression in endothelial cells, supporting endothelial-to-mesenchymal transition in the pathogenesis of cardiac fibrosis (supported by Friedreich's Ataxia Research Alliance). LEARNING OBJECTIVES: The presentation will enable the learner to: 1. Describe endothelial-to-mesenchymal transition in the pathogenesis of cardiac fibrosis in Friedreich cardiomyopathy